Tren‐Cored PAMAM Dendrimer/Silver Nanocomposites: Efficient Colorimetric Sensors for the Determination of Mercury Ions from Aqueous Solutions. Issue 26 (10th July 2019) - Gürbüz, Mustafa U.; Elmacı, Gökhan; Ertürk, Ali S.
Abstract: Contamination through Hg 2+ ions in natural spring waters leads to a major destruction in human health and the universal ecosystem. Therefore, development of rapid, simple and cost‐effective methods for the specific and high sensitive determination of Hg 2+ is of great importance. Among these methods, silver nanoparticles (Ag NPs) are used for the effective colorimetric detection of metal ions facilitating from the changes in the surface plasmon resonance (SPR) band. In this study, we have synthesized dendrimer‐encapsulated Ag NPs (Ag DENPs) by using Tris(2‐aminoethyl)amine (TREN) cored and amine‐terminated generation‐4 poly(amido amine) dendrimer (PAMAM), T4.NH2, as a novel template. The synthesized Ag DENPs were characterized by UV‐Vis, XRD, TEM and further used for the colorimetric and quantitative determination of Hg 2+ ions. The developed Ag DENP sensor was tested against common present cations, Co 2+, Cu 2+, Cd 2+, Pb 2+, Ni 2+ Zn 2+, Ba 2+, Ca 2+, Al 3+, in the environment and found to be specific only for Hg 2+ ions. Furthermore, limit of detection (LOD) for Hg 2+ was found to be 1.18 ppb (5.88 nM). Results revealed that the proposed method can be successfully used with a good sensitivity and selectivity to determine mercury (II) ions in various water samples. Abstract : A new intra‐type dendrimer‐encapsulated Ag NP (Ag DENP) was synthesized by using Tris(2‐aminoethyl)amine (TREN) cored generation‐4 amine‐terminated poly(amido amine) (PAMAM) dendrimer as a novel template for the first time. The prepared Ag DENPs were found as colorimetric active for the selective and sensitive fort the rapid determination of Hg 2+ with a considerably low limit of detection (LOD) (1.18 ppb, 5.88 nM).